Detection of Somaclonal Variation in Micropropagated and Acclimatized Plantlets of Oryza sativa MRQ 74 from Stem Explants - Saleh, A.; Taha, R. M.; Mahmad, N.; Hashimah, Binti Elias; Hamid, H. A. A. (Sociedade Brasileira da Ciência das Plantas Daninhas, 2019)
In plant tissue culture system, the excessive supply of plant growth hormones may inhibit further growth and development of the regenerants and sometimes it may induce somaclonal variation. In this study, the optimum concentration of plant growth hormones for in vitro regeneration of Oryza sativa L. cv. MRQ 74 was identified and subsequently the occurrence of somaclonal variation of regenerated plantlets was determined through cytological analysis of in vivo and in vitro grown plantlets. MS media supplemented with 0.1 mg L-1 BAP in combination with 0.1 mg L-1 NAA was found to be the optimum concentration for shoots and roots induction of Oryza sativa L. cv. MRQ 74. Plantlets derived from MS media supplemented with 0.5 mg L-1 2,4-D showed higher survival rate than that of MS media supplemented with 0.1 mg L-1 BAP in combination with 0.1 mg L-1 NAA. The plant height, number of leaf, leaf length and number of seeds per stalk of acclimatized plants were significantly lower (p<0.05) as compared with plants grown in vivo. Cytological analysis of in vivo and in vitro grown Oryza sativa L. cv. MRQ 74 revealed that the presence of 2,4-D in the culture media had significantly decreased the mitotic index (MI) and increased the ploidy level of the cell nuclei. The findings of the present study would be useful for plant breeders and biotechnologist since somaclonal variation provides a useful source of genetic variation for crop productivity and quality improvement.